Duodenocolonic Fistula As A Rare Complication of Intestinal Burkitt Lymphoma in a Three-Year-Old Boy - Okuda, Kenichi Vinzenz; Laass, Martin; Schuchardt, Katrin; Lange, Björn Sönke; Knöfler, Ralf; Fitze, Guido; Woessmann, Wilhelm; Suttorp, Meinolf (Klinische Pädiatrie, 2018)
Background Burkitt lymphoma (BL) in children often presents with abdominal localization. Intestinal perforations have been described mainly during treatment. We report on a three-year-old patient with abdominal BL who was diagnosed with a duodenocolonic fistula.Case report A three-year-old boy presented with diarrhea, crampy abdominal pain, and a four-week history of loss of appetite and weight. Ultrasound and MRI detected a colonic tumor forming a duodenocolonic fistula which was verified by gastroduodenoscopy. A surgical biopsy revealed BL. The stage III BL with low LDH was treated with four courses of BFM-type short-pulse chemotherapy. After two courses of chemotherapy the patient developed a mechanic ileus. A segmental resection of a short segment of the colon at the right flexure carrying the residual tumor mass with cicatricial stenosis and fistula followed by colonic end to end anastomosis and covering of the fistula by omentum major were carried out without complication. 15 days after surgery, two additional courses of chemotherapy could be administrated and the boy is in ongoing remission and free of any symptoms with a follow-up interval of 18 months.Conclusions Duodeonocolonic fistula at presentation in a child with abdominal BL is extremely rare. Delayed surgery after size of the tumor bulk has been reduced by chemotherapy might represent a risk adapted approach. However, due to limited experience with duodenocolonic fistulas even in larger pediatric lymphoma trials any decision has to be based on the problems to be faced in individual cases.
Keywords: Burkitt lymphoma; duodenocolonic fistula; child; chemotherapy; Pediatric oncology